Positive liberty - David P. Macpherson (Groundings, 2008)
Freedom is a word we hear a lot. Yet it is often unclear what is meant by it. Recent anti-terrorism laws have been argued by some as safeguarding freedoms and argued by others as restricting them. In this paper, I aim to create and defend an explanation of the nature of freedom that is practical and useful. Through offering a set of criteria, and answering potential criticisms, I conclude that “freedom” must consider people’s strongest desires and take into account the multitude of internal barriers to the fulfilment of these desires. Such a definition will hopefully help us gain a clearer understanding of when our liberty is under threat: putting us in a better position to defend it.